Perception of providing training for commercial vehicle driver among SMEs logistics companies / Muhammad Azri Md Hassan - Md Hassan, Muhammad Azri (2015)
Commercial vehicle drivers are the from lines for commercial logistics that ensure safe delivery of goods. When the growing logistics industry in Malaysia and served mostly by SMEs, the training needs of drivers may not be priority than resulting in poor work performance of drivers reflected by many problem that arise due to these drivers. Training, one of the elements in Human Resource should be provided by the SME Logistics Company. The objective of the study are (1)10 identify the current situation in training for commercial vehicle drivers among SME logistics companies in Selangor (2) to examine the factors that can influence driver’s training among SME logistics companies in Selangor and (3) m analyse the most determinant factors affecting driver‘s training among SME logistics companies in Selangor. The study was conducted by a quantitative survey where questionnaire distribution to 226 managels of SMEs logistics companies in Selangor and only 110 of the respondents have given feedback. A conceptual framework was developed based on the extensive literature. This empirical research explored the relationship of independent variable with training needs. The three main variables being studied includes same dimensions that were grounded theory, such as economic return, personal career development and reputation of the company. The relationship between the three valiables showed different significanoe. The variables are significant for economic return of the company and driver's training. But the variables of personal career development and reputation of company it shows there no significance between acceptance of driver training with personal career development of drivers and company’s reputation.